Probiotics Enhance FOLFOX Efficacy Via Gut Bacterial Tryptophan Metabolism in Colorectal Cancer - Deng Yufei; Hou Xiaoying; Chen Kailing; Shao Tong; Liu Yuchen (BIO Web of Conferences)
FOLFOX is the recommended regimen for CRC chemotherapy, but its response rate is limited. Our previous studies confirmed that intestinal microbiota is strongly associated with FOLFOX's anti-CRC effect, but the underlying mechanism remains unclear. In this study, we investigated the effects and potential mechanisms of complex-probiotics on FOLFOX efficacy against CRC based on microbiome and metabolomics analysis. We found that probiotics enhanced FOLFOX's anticancer activity, greatly changed the distribution of gut microbiota and metabolic activity of tumor-bearing mice. Further analysis revealed that level of gut bacterial tryptophan metabolism was significantly correlated with pharmacodynamic indexes of FOLFOX, demonstrating that probiotics may enhance FOLFOX efficacy through gut microbiota tryptophan metabolism. This study provides novel insights as well as potential synergistic strategy of FOLFOX in clinical CRC treatment.